Multi-single plane study on polyethylene terephthalate glycol (PETG) using fused deposition modelling process - Jayabharty, Mogan (2024)
FDM is an AM technique that produces 3D parts layer by layer directly from a CAD model, allowing designers broader creative freedom than is possible with traditional manufacturing techniques. The FDM machine is essentially a gantry machine controlled by computer numerical control (CNC) that has two tiny extruder head nozzles, one for the modelling material and the other for the support material. Multi-plane printing combines several printing planes to perform the layers required to create a 3D part. Due to the workspace geometry, multi-plane layering is impossible with gantry-style 3D printers unless a serial link manipulator or robot arm is attached. However, one of the most prevalent problems with FDM printed items is poor mechanical properties, one of the main limitations restricting its application. Therefore, this study aims to fabricate multi- and single-plane specimens using a gantry style 3D printer and investigate the physical and mechanical properties of multi- and single planes. Due to its durability and excellent impact resistance, PETG polymer is used in this experiment. Orientation angles of 0°-0°, 45°-0° and 90°-0° were printed on multi-plane specimens. In comparison, single-plane specimens were printed in 0°, 45° and 90°. Physical properties are measured in density and dimensional accuracy, while mechanical properties are measured in tensile and flexural strength. Morphology analysis such as OM and SEM have been used to analysed the result obtained. In this study, multi and single-plane specimens were printed using Creality Ender 3 desktop 3D printer and tested the physical and mechanical properties. Based on the results, the tensile properties of multi-plane specimens have significant value compared to single planes. Multi-plane 0°-0° for both concentric and line patterns shows the highest tensile strength of 39.6 MPa and 33.6 MPa, respectively, while single plane 90° exhibits the lowest tensile strength of 11.9 MPa and 5.1 MPa, respectively. Thus, the SEM analysis justifies the results of the tensile strength test. However, multi-planes' flexural strength shows relatively low properties compared to a single plane. The highest flexural strength is single plane 0° with 62MPa, and the lowest is multi-plane 90°-0° at 5.4MPa for the concentric pattern. When considering the physical properties of density and dimensional accuracy, multiplane printing yielded poor results for density compared to single-plane printing. Optical microscope analysis was done to prove the density results. However, single-plane and multiplane printing were equally close to the expected value for dimensional accuracy. From the obtained result, multiplane specimen has significant improvement in tensile strength, while flexural strength was affected due to delamination of layer occurred during testing. The relative density of multi-plane samples is lower compare to single plane, due to void formation during printing. Hence, it can be concluded that multi-planes affect physical properties and also mechanical properties of PETG specimens. Compression test should be done on same material and building orientation for future study. Adding nanoparticles, fibres, and other reinforcements to the raw material to test improvements to the mechanical properties of multi-plane printed specimens also important for future direction.